Challenges and Applications for Implementing Machine Learning in Computer Vision - Kashyap, Ramgopal, 1984- editor.; Kumar, A. V. Senthil, 1966- editor. 624088 (Hershey, PA : IGI Global/Engineering Science Reference, an imprint of IGI Global)
Includes bibliographical and references